An introduction to the spaceport industry : runways to space - Tinoco, Janet K.; Yu, Chunyan; Howard, Diane; Stilwell, Ruth E. (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2020)
"This book provides a contemporary look at spaceports, not only from relevant technological drivers, policies, and legal perspectives, but also from impacts associated with airspace use and aviation stakeholders; economic, business, financial, and environmental considerations; issues facing airports transitioning to air and space ports; as well as spaceport planning. Through case and event studies, research and analysis, along with information obtained through professional experience, this book provides an overview of the many benefits, unique challenges, and issues facing commercial spaceports and spaceport operators. Each chapter is a stand-alone key topic such that the reader can focus on the most compelling issues relevant for him/her or can view the book as an integrated whole for a full perspective. While examples and case studies come largely from the United States, the reader can draw conclusions that are independent of country and situation. Also, information on other nation state policies, advancements, and endeavors, among other topics, is provided to give a global perspective, further expanding the relevancy and benefits of the book to both the domestic and international audiences An Introduction to the Spaceport Industry: Runways to Space fills a gap in the literature, providing students, professors and researchers with deep insights into the fast-growing commercial spaceport industry"--
OCLC-licensed vendor bibliographic record.
Keywords: Space launch industry; Launch complexes (Astronautics); TRANSPORTATION / Aviation / Commercial